Comments on "Unobservable Selection and Coefficient Stability: Theory and Evidence" and "Poorly Measured Confounders are More Useful on the Left Than on the Right". Issue 2 (3rd April 2019) - De Luca, Giuseppe; Magnus, Jan R.; Peracchi, Franco
Abstract–: We establish a link between the approaches proposed by Oster (2019 ) and Pei, Pischke, and Schwandt (2019 ) which contribute to the development of inferential procedures for causal effects in the challenging and empirically relevant situation where the unknown data-generation process is not included in the set of models considered by the investigator. We use the general misspecification framework recently proposed by De Luca, Magnus, and Peracchi (2018 ) to analyze and understand the implications of the restrictions imposed by the two approaches.